Determination of Financial Literacy, Business Strategy and Innovation on Financial Performance of Small and Medium Enterprises (SMEs) Palm Oil Sector in North Aceh Regency - Muhammad Haykal; Muhammad Nazaruddin; Deassy Siska (LPPM Universitas Malikussaleh, 2024)
This study aims to see how financial literacy, business strategy and business innovation affect financial performance in SMEs entrepreneurs in the palm oil sector in North Aceh district. In this study, using the Structural Equation Modeling (SEM) Analysis Moment of Structural (AMOS) equation model using path analysis, to analyze the pattern of relationships between variables with the aim of determining the direct and indirect influence of a set of independent variables (exogenous) on the dependent variable (endogenous). This study found that financial literacy, business strategy have a positive and significant effect on financial performance, while business innovation does not affect financial performance in entrepreneurs. Guidance for entrepreneurs in this business sector must be improved so that business entreprenuer can continue to improve business innovation by providing training, especially regarding innovation in the development of business information technology.